Factors associated with hemoglobin glycation index in adults with type 1 diabetes mellitus: The FGM‐Japan study. Issue 4 (14th February 2023) - Sakane, Naoki; Hirota, Yushi; Yamamoto, Akane; Miura, Junnosuke; Takaike, Hiroko; Hoshina, Sari; Toyoda, Masao; Saito, Nobumichi; Hosoda, Kiminori; Matsubara, Masaki; Tone, Atsuhito; Kawashima, Satoshi; et al.
ABSTRACT: Aims/Introduction: The discrepancy between HbA1c and glucose exposure may have significant clinical implications; however, the association between the hemoglobin glycation index (HGI) and clinical parameters in type 1 diabetes remains controversial. This study aimed to find the factors associated with HGI (laboratory HbA1c − predicted HbA1c derived from the continuous glucose monitoring [CGM]). Materials and Methods: We conducted a cross‐sectional study of adults with type 1 diabetes ( n = 211, age 50.9 ± 15.2 years old, female sex = 59.2%, duration of CGM use = 2.1 ± 1.0 years). All subjects wore the CGM for 90 days before HbA1c measurement. Data derived from the FreeStyle Libre sensor were used to calculate the glucose management indicator (GMI) and glycemic variability (GV) parameters. HGI was defined as the difference between the GMI and the laboratory HbA1c levels. The participants were divided into three groups according to the HGI tertile (low, moderate, and high). Multivariate regression analyses were performed. Results: The female sex ratio, HbA1c, and % coefficient of variation (%CV) significantly increased over the HGI tertile, while eGFR and Hb decreased over the HGI tertile. In multivariate analysis, the factors associated with HGI were %CV and eGFR, after adjusting for HbA1c level and sex ( R 2 = 0.44). Conclusions: This study demonstrated that HGI is associated with female sex, eGFR, and some glycemic variability indices, independently of HbA1c. Minimizing glycemic fluctuations might reduce HGI. This information provides diabetic health professionals and patients with personalized diabetes management for adults with type 1 diabetes. Abstract : This study aimed to investigate factors associated with the hemoglobin glycation index (HGI) indicating a discrepancy between HbA1c and glucose exposure in adults with type 1 diabetes. Female sex ratio, HbA1c, and % coefficient of variation (%CV) significantly increased over the HGI tertile, while eGFR and Hb decreased over the HGI tertile. In multivariate analysis, the factors associated with HGI were %CV and eGFR, after adjusting for HbA1c level and sex ( R 2 = 0.44).